Wireless healthcare monitoring system with ZigBee communication link support. (9th September 2011) - Hamza, N.; Touati, F.; Khriji, L.
We present a framework for a wireless healthcare monitoring system with ZigBee communication link support. It has the capability to monitor vital signs from multiple biosensors. Biomedical signals are collected and processed using two-tier subsystems. The first stage is the mobile device carried on the body that runs a number of biosensors (internal subsystem). At the second stage, further processing is performed by a local base station (external subsystem) using the raw data transmitted on-request by the mobile device. The processed data as well as the analysis results are then monitored and diagnosed through a man–machine interface.